(untitled) (Management and Connections Journal, 2021)
In 2011 the Federal Government created the Brazilian Hospital Services Company (EBSERH), to restructure university hospitals. From then on, several institutions joined the management by the company, including the study organization, which took place in 2015, after approval by the Council of the Federal University of Santa Catarina (UFSC). This article aims to understand the perceptions of workers at the University Hospital (HU/UFSC) in relation to organizational change. The research is characterized as a case study, of a qualitative and descriptive nature. Data collection consists of interviews and non-participant observation, using content analysis. The results of the research demonstrate that joining EBSERH was complex and challenging for people, who brought different reactions and resistance to change. There was also little effective evaluation of the process by the managers, given the limited communication between those involved.